Another Coptic Letter from the Dioscorus Archive in the Collection of the Ghent University Library? - Yasmine, Yasmine; Stolk, Joanne (Chronique d’Égypte, 2024)
Abstract This article presents the first edition of P.Ghent Inv. 48, a sixth-century Coptic letter from the collection of the Ghent University Library. The document references taxes and officials related to the tax collection, indicating a fiscal context. After analyzing the palaeography, linguistic features, prosopography, and historical context, the authors explore a possible connection between the text and the Dioscorus archive.